“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

An Experimental and Computational Modeling Study on Additively Manufactured Micro‐Architectured Ti–24Nb–4Zr–8Sn Hollow‐Strut Lattice Structures - Pramanik, Sudipta; Milaege, Dennis; Hein, Maxwell; Andreiev, Anatolii; Schaper, Mirko; Hoyer, Kay-Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Assessment of mechanical and optical properties of Al 6060 alloy particles by removal of contaminants - Vieth, Pascal; Borgert, Thomas; Homberg, Werner; Grundmeier, Guido (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Characterization and analysis of plastic instability in an ultrafine‐grained medium Mn TRIP steel - Teng, Zhenjie; Wu, Haoran; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Zhang, Hanlon; Boller, Christian; Starke, Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Characterization and Analysis of Plastic Instability in an Ultrafine‐Grained Medium Mn TRIP Steel - Teng, Zhenjie; Wu, Haoran; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Zhang, Hanlong; Boller, Christian; Starke, Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Modification of Iron with Degradable Silver Phases Processed via Laser Beam Melting for Implants with Adapted Degradation Rate - Krüger, Jan Tobias; Hoyer, Kay-Peter; Andreiev, Anatolii; Schaper, Mirko; Zinn, Carolin (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Atomic Layer Deposition of Copper Metal Films from Cu(acac) 2 and Hydroquinone Reductant - Tripathi, Tripurari Sharan; Wilken, Martin; Hoppe, Christian; de los Arcos, Teresa; Grundmeier, Guido; Devi, Anjana; Karppinen, Maarit (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Influence of Microstructure in Near‐Surface Areas of Feedstocks on the Bond Strength of Roll Bonded Aluminum Clads - Grydin, Olexandr; Matzelt, Manuel; Andreiev, Anatolii; Frolov, Yaroslav; Schaper, Mirko (Advanced Engineering Materials)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Relationships between Microstructural and Mechanical Performance on Example of an Air‐Hardening Steel - Grydin, Olexandr; Andreiev, Anatolii; Zogaj, Mergim; Frolov, Yaroslav; Schaper, Mirko (Advanced Engineering Materials)

Additive Manufacturing of Porous Structures for Unmanned Aerial Vehicles Applications - Klippstein, Sven Helge; Hassanin, Hany; Diaz De Cerio Sanchez, Alejandro; Zweiri, Yahya; Seneviratne, Lakmal (Advanced Engineering Materials)

Fused Deposition Modeling for Unmanned Aerial Vehicles (UAVs): A Review - Klippstein, Sven Helge; Diaz De Cerio Sanchez, Alejandro; Hassanin, Hany; Zweiri, Yahya; Seneviratne, Lakmal (Advanced Engineering Materials)
Additive Manufacturing (AM) is a game changing production technology for aerospace applications. Fused deposition modeling is one of the most widely used AM technologies and recently has gained much attention in the advancement of many products. This paper introduces an extensive review of fused deposition modeling and its application in the development of high performance unmanned aerial vehicles. The process methodology, materials, post processing, and properties of its products are discussed in details. Successful examples of using this technology for making functional, lightweight, and high endurance unmanned aerial vehicles are also highlighted. In addition, major opportunities, limitations, and outlook of fused deposition modeling are also explored. The paper shows that the emerge of fused deposition modeling as a robust technique for unmanned aerial vehicles represents a good opportunity to produce compact, strong, lightweight structures, and functional parts with embedded electronic.
Keywords: FDM; Review; UAV

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Influence of the Surface and Heat Treatment on the Bond Strength of Galvanized Steel/Aluminum Composites Joined by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Grothe, Richard; Schmidt, Hans Christian; Hordych, Illia; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
The influence of a chemical or mechanical surface modification followed by different post-heat treatments on the bond strength of galvanized steel/ aluminum composites is studied. An incremental rolling process is used for joint formation based on plastic deformation. The morphology, the chemical state of the modified surfaces as well as the cross-section, and local potential distribution of the welded zone is characterized by different microscopic and spectroscopic methods. The stability of the joint is analyzed by a shear-force test in combination with microscopic failure analysis. A clear correlation between pre/post-treatment and the joint strength is observed.

Molecular Engineering of Aluminum-Copper Interfaces for Joining by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Voigt, Markus; Schmidt, Hans Christian; Rodman, Dmytro; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
Interface modification based on ultra-thin mercapto-propyl(trimethoxy) silane (MPTMS) films is shown to promote joining of copper and aluminum by plastic deformation followed by a heat treatment. The surface morphology and the surface chemistry of the metal substrates were analyzed by means of FE-SEM, XPS, and FT-IRRAS. The spectroscopic data show that the MPTMS film is crosslinked via Si-O-Si bonds and that stable Cu-S and Si-O-Al interfacial bonds are formed. The shear-force tests of the joints led to force displacement curves that are characteristic for a covalently bonded interface. Complementary cross sectional SEM and EDS analysis of the joint proved that a defect-free interface was formed without any measureable interdiffusion of metals across the interface or cracking of an oxide films.

On the way to identify microorganisms in drinking water distribution networks via DNA analysis of the gut content of freshwater isopods - Mayer, Michael; Keller, Adrian; Szewzyk, Ulrich; Warnecke, Hans-Joachim (Journal of Biotechnology)

Functionally Graded Alloys Obtained by Additive Manufacturing - Niendorf, Thomas; Leuders, Stefan; Riemer, Andre; Brenne, Florian; Tröster, Thomas; Richard, Hans Albert; Schwarze, Dieter (Advanced Engineering Materials)

X-Ray Photoelectron Spectroscopy Investigations of the Surface Reaction Layer and its Effects on the Transformation Properties of Nanoscale Ti51Ni38Cu11Shape Memory Thin Films - König, Dennis; Naujoks, Dennis; de los Arcos de Pedro, Maria Teresa; Grosse-Kreul, Simon; Ludwig, Alfred (Advanced Engineering Materials)

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)